Analisis Persepsi Masyarakat Terhadap Komunitas Peduli Lubang Jalanan di Kota Malang - Faizal Kurniawan (SIMULACRA: JURNAL SOSIOLOGI, 2018)
Malang Raya with all the trimmings is a city with intense activity. As a result, the streets in most areas in Malang became commonly used. The volume density of vehicles per day resulted in a lot of potholes. However, the slow handling of city government and county government resulted in the holes in the road more and more common. Of course this led to frustration for road users. Many victims of accidents caused fall due pit road. Not the least of casualties caused by potholes is pushing a bunch of young for forming Social Community “Peduli Lubang”. The group is moved voluntarily. Social counciosness encouraging to form this community. In its action, they make a circular mark or ledges with pylox white against the hole in every street. The goal is sign that the road users see the white markings they have made. The sign is effective because Driver can seen from distance before the hole, finally the driver can reduce speed. A lot of appreciation given to this community. Remaining so many hole in streets, and the number of "Self founding" that they have to spend for the sake of this social action. Their action also received a response from the mayor. This research uses a case study approach and indepth interview methods to community members and resource persons also road users to recognize the existence of this grass-roots communities. Observations made to this community by following all the activities of this group. As a result, the public perception of these two groups divided into two: the pros and cons of their action. Part of the counter on the excuse that their sentences are inappropriate for display in public facilities. In conclusion the public perception of the pro-grassroots movement may be resistance to the government policy terksan slow in dealing with this issue. Evidenced by the more intense they carry out an action, response Malang city and county governments more quickly. Expected social consciousness is what will encourage Malang city and county governments to be more sensitive to sound that good netizens on social media and direct aspiration.